Vitrocerâmicas de silicato de lítio com gradientes microestruturais - simulações e experimentos - Souza, Thalia Delmondes de (Universidade Federal de São Carlos, 2022)
The microstructure of glass-ceramics (GCs) depends on their chemical composition and thermal history, from the cooling of the precursor glass to the heat treatments. In glass production, the cooling rate on the surface is much higher than in the center, allowing the appearance of crystal nuclei in the central parts that cause microstructural heterogeneities in the GC. Furthermore, during the heat treatments, temperature gradients appear in relatively thick or large samples and, consequently, microstructures with different numbers and sizes of crystals will be obtained along the part, causing deterioration of its mechanical properties. In this work, vitreous samples based on the Li2O-SiO2 system were prepared to evaluate the effects of different sample sizes on the appearance of thermal gradients along the two stages of obtaining GCs (cooling and thermal treatments). The heat exchange in these steps and the thermal gradients generated were numerically simulated and the impact of these gradients on the microstructure and mechanical properties of the GCs was analyzed. For that, the glass-forming liquid was poured into copper and 304 stainless steel molds and, from a thermal treatment of crystal growth and optical microscopy analysis, the existence of microstructural gradients caused by nuclei formed in the cooling was evaluated. After nucleation and growth heat tratament, samples from each mold were analyzed by Scanning Electron Microscopy, Biaxial Bending and X-Ray Diffraction. The results indicated that an increase in the size of the mold and the glass produced leads to the appearance of crystalline nuclei inside the part during cooling. However, after the heat treatments of nucleation and crystal growth, the existence of pre-nucleation does not cause significant heterogeneities in the GC. On the other hand, heat treatments in samples with 14 x 45 mm (diameter x height), promote significant thermal gradients and the existence of microstructural gradients, reducing their mechanical properties.
Lithium silicate glass ceramics with microstructural gradients - simulations and experiments
Keywords: Vitrocerâmica; Dissilicato de lítio; Gradiente térmico; Microestrutura; Propriedades mecânicas; Glass ceramic; Lithium disilicate; Thermal gradient; Microstructure; Mechanical properties; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS